Optimasi Kecepatan Kereta Api Menggunakan Metode Kontrol Model Prediksi - Pamor Gunoto (Politeknik Negeri Batam, 2013)
On a railway network systems, railway timetable is veryimportant part of a systems because it involves a very complex. A delay of single train can cause a continuity affect of other trains that cause the scheduling system will experience a very significant change. One solution that is used to minimize the train delay by optimization the speed of train. In this research using methode of model predictice control (MPC) for design model by controlled. The result model implementation is average speed of 57,9 km/hours.